2023
DOI: 10.3960/jslrt.22042
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced PD-L1 expression on tumor cells in primary CD30-positive cutaneous large T-cell lymphoma: a report of lymph node lesions of four cases

Abstract: Scarce data are available regarding neoplastic PD-L1 (nPD-L1, clone SP142) expression in cutaneous T-cell lymphoma. We recently documented a possible association of increased nPD-L1 expression with tumor progression to secondary nodal involvement in two cases of CD30-positive primary cutaneous large T-cell lymphoma (PC-LTCL) (Pathol Int 2020;70:804). Notably, the nodal sites exhibited classic Hodgkin lymphoma (CHL) mimicry related to both morphology and tumor microenvironment (TME), i.e., abundant PD-L1-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These findings support the concept that neoplastic PD-L1 expression in CTCL increases with lymphoma progression. In addition, Takahashi et al noted that the nodal lesions of PC-ALCL had a tumor microenvironment rich in PD-L1-positive TAMs with scarce PD-1 expression on T-cells very similar to that observed in cHL [ 102 ]. Although further studies are required to understand the mechanisms underlying PD-L1 expression in PC-ALCL and other CTCLs, the findings of high PD-L1 expression in tumor cells and TAMs of PC-ALCL with nodal involvement may have therapeutic implications for the use of ICIs in this setting of patients.…”
Section: Alcl and Pd-1/pd-l1 Axismentioning
confidence: 94%
See 2 more Smart Citations
“…These findings support the concept that neoplastic PD-L1 expression in CTCL increases with lymphoma progression. In addition, Takahashi et al noted that the nodal lesions of PC-ALCL had a tumor microenvironment rich in PD-L1-positive TAMs with scarce PD-1 expression on T-cells very similar to that observed in cHL [ 102 ]. Although further studies are required to understand the mechanisms underlying PD-L1 expression in PC-ALCL and other CTCLs, the findings of high PD-L1 expression in tumor cells and TAMs of PC-ALCL with nodal involvement may have therapeutic implications for the use of ICIs in this setting of patients.…”
Section: Alcl and Pd-1/pd-l1 Axismentioning
confidence: 94%
“…Kentekure et al reported increased PD-L1 expression in tumor cells in MF showing disease progression and large cell transformation [ 100 ]. Recently Takahashi et al, identified four cases of PC-ALCL that developed secondary nodal involvement and interestingly found that PD-L1 expression in neoplastic cells greatly increased with tumor progression to nodal involvement [ 101 , 102 ]. PD-L1 expression was =/>50% of lymphoma cells in nodal disease, whereas it was rarely detectable or very low (=/<1%) when the disease was limited to the skin [ 101 , 102 ].…”
Section: Alcl and Pd-1/pd-l1 Axismentioning
confidence: 99%
See 1 more Smart Citation